Cost Burden and Accessibility: Analysis of Indonesian Household Energy Expenditure - Audhi Ahmad Balya; Marcella Alika Hutabarat; Djoni Hartono (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
The Main Objectives of this study are to check whether Indonesian households suffer from energy poverty or not, as well as to determine the accessibility to certain modern energy accesses (LPG and Electricity) and the energy cost burden that Indonesian households must bear. Using data from SUSENAS 2014, this research is conducted by utilizing descriptive statistics analysis and Cross-Section OLS to achieve the objectives. It was found that there is no single Island Cluster in Indonesia suffers from energy cost burden. There are also differences in accessibility of modern energy and its relation to energy expenditure, especially in Maluku and Papua.